The Effect of Human Capital on Economic Growth: The Case of Türkiye - Çanakci, Burak; Taşar, Izzet (IGI Global Scientific Publishing, 2026)
The concept of human capital emerged with the realization that economic growth cannot be explained solely by changes in physical capital. In this context, human capital is directly related to factors such as education, health to increase the productivity of individuals and their contribution to the economy. Economic growth is defined as the increase in the production of goods and services over time. However, the fact that this increase is sustainable and increases the welfare of the society shows the importance also investments in human capital. TDenison, Mankiw-Romer-Weil, Becker-Schultz and Jorgenson approaches from neo-classical growth models and Barro, Lucas and Charles Jones approaches from endogenous growth models are examined as economic approaches that focus on the effect of human capital on economic growth. In this study, which is specific to Türkiye, the long-term relationship between human capital and economic growth is examined in Türkiye with the GDP and human capital index between the years 2000-2022. Copyright © 2026, IGI Global Scientific Publishing. Copying or distributing in print or electronic forms without written permission of IGI Global Scientific Publishing is prohibited. Use of this chapter to train generative artificial intelligence (AI) technologies is expressly prohibited. The publisher reserves all rights to license its use for generative AI training and machine learning model development.
Keywords: Economic analysis; Economic and social effects; Electronic publishing; Growth (materials); Inflation; Investments; Learning systems; Machine learning; Economic approach; Economic growths; Education healths; Endogenous growth model; Good and services; Growth models; Human capital growths; Human capitals; Human economics; Long-term relationships; Copyrights